2022
DOI: 10.48077/scihor.25(12).2022.90-101
|View full text |Cite
|
Sign up to set email alerts
|

Export performance of Indonesian Swallow's Nest commodities in main destination countries

Abstract: The trend of increasing exports of Indonesian swallow's nests and the high market potential shown by increased consumption requires Indonesia as one of the main producers of swallow's nests to be able to seize the existing market opportunities. This study aims to determine the export performance of Indonesian swiftlet nests in the main destination countries. The method used in this research is Constant Market Share. The secondary data used is time series data collected from 2011 to 2020. Based on Constant Mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…According to Asrol (2017), there are four terminologies for measuring competitiveness with the CMS model: standard growth effects, commodity effects, market distribution effects, and competitiveness effects. The CMS approach has been applied in a study on developing export markets for agriculture (Prasetyo, Marwanti and Darsono, 2018;Jamilah et al, 2022;Rahmawati, Hadi Purnomo and Marwanti, 2022;Tety, Kurnia and Andriani, 2022) and food processing products by Widodo et al, (2008). Based on Tires, Philips, and Lim (1985) in Widodo et al, (2008), the CMS model can be written as follows: : Total export value of all Indonesian commodities in year t-1 (US$) E(t-1)i :…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Asrol (2017), there are four terminologies for measuring competitiveness with the CMS model: standard growth effects, commodity effects, market distribution effects, and competitiveness effects. The CMS approach has been applied in a study on developing export markets for agriculture (Prasetyo, Marwanti and Darsono, 2018;Jamilah et al, 2022;Rahmawati, Hadi Purnomo and Marwanti, 2022;Tety, Kurnia and Andriani, 2022) and food processing products by Widodo et al, (2008). Based on Tires, Philips, and Lim (1985) in Widodo et al, (2008), the CMS model can be written as follows: : Total export value of all Indonesian commodities in year t-1 (US$) E(t-1)i :…”
Section: Methodsmentioning
confidence: 99%
“…This positive value also shows that Indonesia can distribute and control these three countries' export markets. The results of research from Rahmawati, Hadi Purnomo and Marwanti (2022), showed that the market distribution effect on other agricultural products also has a positive value in the Chinese market share, where China is the largest export destination country that has a high demand. Furthermore, the market distribution effect to Japan and Singapore shows a negative value with an average of -0.00000040 and -0.00000009.…”
Section: The Market Distribution Effectmentioning
confidence: 99%